Perioperative blood loss reduction using a sterile exsanguination tourniquet for orthopedic femoral-related surgeries in children: a randomized controlled study - Rattanathanya T. (2023)
OBJECTIVES: The sterile exsanguination tourniquet (SET) could be an alternative for providing bloodless surgeries in orthopedic femoral-related surgeries in pediatric patients where the standard pneumatic tourniquet would not be feasible. This randomized-controlled study aimed to evaluate the efficacy of SET in decreasing total perioperative blood loss and blood transfusion. METHODS: We conducted an unplanned interim analysis of data from a randomized-controlled trial. At the time of the analysis, 31 pediatric patients had been randomly assigned to undergo surgery with the SET application (the SET group, 15 patients) and without the SET application (the control group, 16 patients). An intention-to-treat analysis was performed to evaluate the total perioperative blood loss, postoperative blood transfusion, estimated intraoperative blood loss, total drainage volume, postoperative hemoglobin level, and operative time according to the significance level adjusted for multiplicity (p < 0.029). RESULTS: There was a borderline statistically significant lower body weight-adjusted TBL in the SET group (SET = 14.1 (7.7, 16.9) ml/kg vs. control 18.3 (14.8, 37.2) ml/kg, p-value = 0.027). The body weight-adjusted transfusion volume was statistically significantly greater in the control group (SET = 0.0 (0.0, 0.0) ml/kg vs. control = 2.1 (0.0, 9.7) ml/kg, p = 0.017). Body weight-adjusted estimated intraoperative blood loss was significantly lower in the SET group (SET = 0.8 (0.2, 3.5) ml/kg vs. control = 5.6 (3.4, 21.5) ml/kg, p < 0.001). In addition, the operative time was lower in the SET group with borderline statistical significance (SET = 105 (85.0, 125.0) vs. control = 130 (101.3, 167.5), p =  0.039). CONCLUSION: Utilization of a sterile exsanguination tourniquet (SET) significantly reduced an estimated intraoperative blood loss while preventing the need for blood transfusion after pediatric orthopedic femoral-related surgeries. Trial registration TCTR20220412003.